A dissection of the Protection, Promotion, Development and Management of indigenous Knowledge Systems Act 6 of 2019: substantive issues and foreseeable consequences for creative industries in South Africa - Zondi, Nokwanda Bathabile (Department of Commercial Law, 2022)
Indigenous knowledge is a broad term that is used to describe various knowledge systems that are intimately linked with traditional communities.1 It is communicated orally and stored in the memories of people belonging to traditional communities; it is also expressed through the art of traditional communities, their practices, community laws, cultural values, folklore, proverbs and activities. 2 The World Intellectual Property Organization (WIPO), defines ‘indigenous knowledge' as a living body of knowledge - know-how, skills and practices that are formed, sustained and passed on through generations of a traditional community, often forming part of its cultural or spiritual identity.3 There is no internationally accepted definition of indigenous knowledge as the protection of indigenous knowledge is a recent discourse amongst relevant global institutions and countries protecting intellectual property. The term ‘traditional knowledge' is sometimes used in place of ‘indigenous knowledge' and this may create confusion. Therefore, for the purposes of this dissertation, it must be noted that these terms are used interchangeably. Furthermore, it must be expressly established that indigenous knowledge is the property of indigenous communities. Indigenous communities, in their interaction with the environments in which they have resided, have developed a body of knowledge, skills and creative expressions over the centuries and this knowledge has formed an integral part of their cultural heritage.4 Such knowledge is now termed indigenous or traditional knowledge and as the true and original creators of such knowledge, indigenous communities are the rightful owners of it. Such ownership is recognized in Article 31 of the United Nations Declaration on the Rights of Indigenous Peoples which states that indigenous peoples have the right to maintain, protect and develop their own cultural heritage, traditional knowledge, and cultural expressions. 5 All claims on the infringement of the ownership right on indigenous knowledge, which shall follow, are based on this recognition of ownership rights held by indigenous communities in their indigenous knowledge.